PENGARUH KOMPOS JERAMI PADI PLUS TITHONIA DAN BIOCHAR TERHADAP SIFAT KIMIA TANAH SAWAH - Muhammad Lucky; Syafrimen Yasin; Gusnidar Gusnidar (Jurnal AGROHITA: Jurnal Agroteknologi Fakultas Pertanian Universitas Muhammadiyah Tapanuli Selatan, 2020)
The low level of soil fertility resulted the decrease of productivity intensification of rice fields. One of the effort is conducted by farmers to improve the fertility are continous application of synthetic fertilizer (PS). Intensive use made PS cause pollution and soil damage. This study was aimed to identification at the best combination the straw plus tithonia compost (J+T) and biochar to improving soil chemical properties intensification of rice fields, and than look effect of increasing compost (J+T) and biochar to soil chemical properties intensification of rice fields. This research was conducted in rice fields in Kuranji, Padang City, West Sumatera. The experimental design used a rondomized complete blok design. The treatments were 0% compost (J+T) and 0% biochar; 100% compost (J+T); 75% compost (J+T) and 25% biochar; 50% compost (J+T) and 50% biochar; 25% compost (J+T) and 75% biochar; 100% biochar. The data were analyzed the variance using F-test DNMRT 5% level. The result showed that the 25% compost (J+T) and 75% biochar the best combination to improvement soil chemical properties intensification of rice fields, that dosage increased soil pH by 6,30; Eh 65,00 mV; organic C 2,53%; organic M 4,35%; total N 0,93%; available P 26,00 ppm; CEC 40,48 cmol(kg)-1; exchangeable K 1,47 cmol(kg)-1; exchangeable Ca 1,06 cmol(kg)-1; exchangeable Na 0,67 cmol(kg)-1; exchangeable Mg 0,57 cmol(kg)-1.